Pembentukan Undang-Undang yang Mengikuti Perkembangan Masyarakat - Pandiangan, Riris Valentina; Nabilah, Azza Rahma; Pusvitasari, Jelita; Susanti, Pipi (VISA: Journal of Vision and Ideas, 2024)
A law is a statutory regulation whose drafting requires a long time and lengthy procedures, as implemented in Law Number 12 of 2011 concerning Making Regulations. The stages of forming a statutory regulation start from planning, drafting, discussing, ratifying or determining, and ratifying. Legislation, especially laws, must be drafted well because they have an impact on both the state and society. However, if the preparation of statutory regulations takes a long time, then the public's demands for legal clarity cannot be met. Moreover, the rules designed to regulate events on the continent will increasingly lag behind the rapidly changing social developments of society. Therefore, solutions are needed to overcome problems related to regional development. For example, it allows the formation of very long laws and regulations through the government in lieu of laws (perpu) by taking into account the community's need for legal certainty. Additionally, thanking existing organizations for conducting research into issues that are no longer in line with societal growth might be a good way to go. So it can be a good recommendation in the revision of Regulation Number 12 of 2011.